A new image of plantain diversity assessed by SSR, AFLP and MSAP markers - (:unkn) unknown (My University, 2005)
Using both SSR and AFLP markers, the genetic diversity of 30 plantains constituting a representative sample of the phenotypic diversity was assessed. The results confirmed a very narrow genetic base of this cultivar group. SSR and AFLP data support the hypothesis that these cultivars may have arisen from vegetative multiplication of a single seed. MSAP were used to survey cytosine methylation status at CCGG sites in order to obtain an alternative source of diversity data. A higher degree of polymorphism was revealed allowing the classification of the samples into three clusters. No correlation was observed between the phenotypic classification and methylation diversity. Implications for breeding programs are discussed.
Keywords: African Research